2011
DOI: 10.1002/j.1839-4655.2011.tb00228.x
|View full text |Cite
|
Sign up to set email alerts
|

A new form of energy poverty is the hallmark of liberalised electricity sectors

Abstract: The restructuring of electricity sectors has resulted in households paying significantly higher prices. Some European prices rose by more than 100 per cent between 2000 and 2010. NSW households experienced an 80 per cent increase during the period 2007 to 2012. Growing numbers of low-income and vulnerable households are spending higher proportions of disposable income on energy bills and, we contend, suffer deprivation and social exclusion as a result. This phenomenon, we posit, is a new form of energy poverty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 16 publications
(15 reference statements)
1
43
0
Order By: Relevance
“…It is likely that the increased awareness regarding energy poverty may be a result of the perceived risk of energy market liberalization. As observed in several countries around the world [12], this process can be associated with significant increases in energy prices-a key factor that contributes to the "development" of energy poverty.…”
Section: Policy Measures In the Area Of Fuel Povertymentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that the increased awareness regarding energy poverty may be a result of the perceived risk of energy market liberalization. As observed in several countries around the world [12], this process can be associated with significant increases in energy prices-a key factor that contributes to the "development" of energy poverty.…”
Section: Policy Measures In the Area Of Fuel Povertymentioning
confidence: 99%
“…However, the practical difficulties of monitoring energy service use within the home mean that this method is likely the least feasible out of all options presented. Finally, a high-level assessment of energy poverty at a national level could be performed based on multiple dimensions or an aggregated indicator that covers several macro indicators following the examples provided by Chester and Morris [12], Tirado Herrero and Bouzarovski [44] and Wang, Wang, Li and Wei [18]. Such assessments could be adjusted to make use of readily available statistics, but their accuracy may be limited.…”
Section: Measuring Fuel Poverty In the Eumentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the literature indicated that the primary eff ect of the reforms in the electricity markets in the EU have been rising prices (Chester, Morris, 2011;Moreno et al 2012;Stankova et al 2010). Due to the fact that electricity prices represent a signifi cant portion of a businesses's costs it can be assumed that price developments should impact on economic growth.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in the long term electricity prices for households increased to a lesser extent in countries where prices were subject to ex ante regulation. Results of studies of Chester and Morris (2011) additionally show that the eff ects of reforms in the electricity markets were felt mainly by the poorest. As they underlined "some European prices rose by more than 100 percent between 2000 and 2010.…”
Section: Literature Reviewmentioning
confidence: 99%